Two-photon excitation photosensitizers for photodynamic therapy: From small-molecules to nano-complex systems - Juvekar, Vinayak; Joon Lee, Dong; Gwan Park, Tae; Samanta, Rohit; Kasar, Pallavi; Kim, Chaeyoon; Rotermund, Fabian; Kim, Hwan Myung (Coordination Chemistry Reviews, 2024)
Two-photon excitation photodynamic therapy (TP-PDT), which uses near-infrared light (>700 nm) as an excitation source, is an essential approach for modern deep-tissue phototherapy. TP offers the advantage of enhanced spatial precision, which enables targeted treatment without harming the surrounding healthy tissue. This review focuses on the recent developments in TP-activating photosensitizers (TP-PSs), which are key agents in TP-PDT. We begin with a brief description of the concept of TP-PDT and then we summarize the recent developments in various types of TP-PSs. We introduce various types of small-molecule-based photosensitizers, specific organelle targeting, and activation strategies using biomolecules, transition metal complexes, and nanocomplex systems. For clarity, we have provided a limited number of TP-PSs characterized by systematic and well-structured approaches. This reveals the promising future of TP-PDT as an innovative therapeutic approach.
Keywords: Deep-tissue therapy; Photodynamic therapy; Photosensitizer; Two-photon excitation